Leveraging Technology for Dengue Fever Management Using Mobile Health GIS and Big Data to Improve Epidemic Control in Tropical Regions: A Literature Review - Nabilla Salsabilla Zainudin, Alifia; Prawiragara, Fachrizal Arfani (Journal of Diverse Medical Research: Medicosphere, 2025)
Background: Dengue Fever (DBD) remains a major public health issue in tropical countries, including Indonesia, leading to significant morbidity and mortality, particularly among children and young adults. With the increasing number of outbreaks, innovative approaches are necessary for effective management. Technological advancements, including mobile health applications (mHealth), Geographic Information Systems (GIS), and big data analytics, have been identified as valuable tools in the early detection, monitoring, and control of Dengue Fever. These technologies promise to improve the efficiency of health systems and expedite the response to outbreaks.Objective: This study aims to explore the role of technology in managing Dengue Fever outbreaks, focusing on the application of mHealth, GIS, and big data in enhancing public health responses and epidemic control efforts.Methods: A literature review was conducted using databases such as PubMed, Google Scholar, and Scopus, with keywords including "Dengue Fever," "mHealth," "GIS," "big data," and "epidemic control." The selected studies, published between 2018 and 2023, were peer-reviewed articles, case studies, and research reports that discussed technological applications in Dengue Fever management.Results: The findings highlight several technological innovations, including the use of mHealth applications for raising public awareness and enabling real-time communication between health workers and the community. GIS technologies are instrumental in mapping high-risk areas for mosquito breeding and planning targeted vector control interventions. Big data analytics allows for the prediction and monitoring of outbreaks, facilitating better resource allocation and more efficient response strategies. These technologies, when integrated, have shown promise in improving Dengue Fever control, particularly in low-resource settings.